Influence of ecological momentary assessment study design features on reported willingness to participate and perceptions of potential research studies: an experimental study. Issue 7 (30th July 2021) - Smyth, Joshua M; Jones, Dusti R; Wen, Cheng K F; Materia, Frank T; Schneider, Stefan; Stone, Arthur
Abstract : Objective: Intensive ambulatory assessment, such as ecological momentary assessment (EMA), is increasingly used to capture naturalistic patient-reported outcomes. EMA design features (eg, study duration, prompt frequency) vary widely between studies, but it is not known if such design decisions influence potential subjects' willingness to participate in a study. We hypothesise that intentions to participate will be higher in studies that are less burdensome and have higher reward (eg, compensation). Design: This experimental study examined if four EMA study design features (study duration, prompt frequency, prompt length, compensation) affected intentions to participate in a hypothetical EMA study and participation appraisals (eg, participation effort). Participants were randomly assigned to conditions (reflecting a fully crossed design of the four features, each with two levels). Each condition presented a vignette describing a study (each a unique combination of design features) and asked them to report on likelihood of participating and study appraisals. Participants: A convenience sample of participants (n=600; 46% female, M age=40.39) were recruited using an online service. Primary and secondary outcome measures: Primary outcomes were willingness to participate (No/Yes) and reported participation likelihood (0–100 scale). Secondary outcomes included appraisals of interest, enjoyment, effort, and if the study makes a valuable contribution to science. Results: We examined main effects, and two-way interactions for participation likelihood, across study design features. Overall, reported willingness to participate and participation likelihood were high (89%, M =83.90, respectively). Shorter study duration, fewer prompts, shorter prompts and higher compensation increased willingness to participate and elicited higher participation likelihood (each associated with ~6%–8% increases). Findings suggested that more intensive studies were judged as somewhat less interesting and enjoyable, and requiring more effort. Conclusion: Hypotheses were generally supported. Design features influence behavioural intentions to participate in, and appraisals of, EMA studies. Implications for participant recruitment and generalisability, and remaining research questions, are discussed.